1997
DOI: 10.1016/s0006-3495(97)78913-6
|View full text |Cite
|
Sign up to set email alerts
|

Probing the ethanol-induced chain interdigitations in gel-state bilayers of mixed-chain phosphatidylcholines

Abstract: Using high-resolution differential scanning calorimetry (DSC), we have studied the effects of ethanol concentrations, [EtOH], on the main phase transition temperatures (T[m]) of the following mixed-chain phosphatidylcholines (PCs): C(15):C(17)PC, C(17):C(15)PC, and C(12):C(20)PC. These lipids have a common molecular weight; however, their apparent acyl chain-length differences between the sn-1 and sn-2 acyl chains, delta C, are distinctively different. The delta C values for these three mixed-chain PCs are, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…For a centrosymmetric electron density profile such as occurs with a lipid bilayer, the phase information for each diffraction order is either ϩ1 or Ϫ1. The only combination of phases that gave a profile consistent with a phospholipid bilayer structure is (Ϫ Ϫ ϩ), in agreement with the observations of numerous x-ray diffraction studies of gel phase DPPC (e.g., see Wiener et al, 1989) and of chain-interdigitated lipid gel phases (for examples, see Furuike et al, 1999;Nambi et al, 1988;Hirsh et al, 1998;Huang and McIntosh, 1997). Fig.…”
Section: X-ray Diffractionsupporting
confidence: 87%
“…For a centrosymmetric electron density profile such as occurs with a lipid bilayer, the phase information for each diffraction order is either ϩ1 or Ϫ1. The only combination of phases that gave a profile consistent with a phospholipid bilayer structure is (Ϫ Ϫ ϩ), in agreement with the observations of numerous x-ray diffraction studies of gel phase DPPC (e.g., see Wiener et al, 1989) and of chain-interdigitated lipid gel phases (for examples, see Furuike et al, 1999;Nambi et al, 1988;Hirsh et al, 1998;Huang and McIntosh, 1997). Fig.…”
Section: X-ray Diffractionsupporting
confidence: 87%
“…It is possible that these aggregates are not indolicidin aggregates but rather pure lipid or lipid-peptide structures. It has been reported that modiWcations to the acyl chains of the phosphatidylcholine that aVect chain length asymmetry or the position of the unsaturation can prevent small amphiphiles such as alcohols from inducing lipid interdigitation, in which the acyl chains of the upper leaXet lipids cross the mid-plane of the bilayer to interpenetrate the acyl chains of the lower leaXet lipids (Huang and McIntosh, 1997;Li et al, 1996;McIntosh et al, 2001). It is likely that the asymmetric chain conWguration of the SM lipid prevents indolicidin from reducing the thickness of the Chol/SM enriched domains.…”
Section: Discussionmentioning
confidence: 99%
“…Solute permeability is determined by the magnitude of membrane/water partition coefficients and is effected by both solute structure and membrane composition (Sarmento et al, 1993, Finkelstein, 1976, Diamond and Katz, 1974, Xiang and Anderson, 1994. Not only does the membrane dictate total solute permeability, but the solute likewise influences the structural and physical properties of the membrane (Huang and McIntosh, 1997).…”
Section: Introductionmentioning
confidence: 99%